EXTH-04. PATIENT-DERIVED CELLS FOR EX VIVO DRUG SCREENING STUDIES OF GLIOMAS. (14th November 2022) - El-Heliebi, Amin; Urbanic-Purkart, Tadeja; Mahdy-Ali, Kariem; Skofler, Christina; Gerlitz, Lisa; Stanzer, Stefanie; Franz, Joakim; Harbusch, Nora; Madl, Tobias; Widhalm, Georg; Rössler, Karl; Tomberger, Martina; et al.
Abstract: BACKGROUND: In precision oncology ex vivo drug screening systems have the potential to improve clinical outcomes. Traditionally, cancer drugs are tested on cancer cell line models, but these cannot represent an individual patient and are biologically too distinct. Drug screening systems usually rely on viability assays and correlations to genomic alterations. Beside genomic alterations, the cellular metabolism is significantly altered which may lead to drug resistance. Here we aim to establish a drug screening platform using tumor cells derived directly from the individual patient glial tumor tissue, create patient derived tumor cells (PDCs) and combine the outcomes from standardized viability- and genetic-assays with a new developed metabolomics platform. Materials and METHODS: Fresh native tissue from patients harbouring low- and high-grade glioma are collected (n=46). Tumor tissue used for NMR-based metabolomic analyses and targeted sequencing analyses as well as PDC isolation. To preserve the original tumor similarity, tissue is short term cultured for two weeks, and PDCs are seeded and treated with a panel of clinical- and preclinical drugs followed by viability assessment, sequencing and metabolomic profiling. RESULTS: Culturing of PDCs is successful in ≥ 85% of patient cases, provided that at least 2 g of tumor tissue is available. The automatized high throughput ex vivo drug response identifies drug candidates, which might become relevant for therapeutic approaches in future. It is possible to distinguish between IDH1 -wild-type and IDH1 -mutant tumors based on the metabolomic profile, which is confirmed by immunohistochemical staining and molecular analysis of IDH1 R132H-mutation. Strong metabolomic variations have been identified, including GABA, lactate, and myo-inositol levels between tumor and healthy tissue. CONCLUSION: Entangling drug screening and genetic assays with metabolomic profiling of glial tumors enriches the information about cellular drug response and paves the way for future clinical studies and better understanding of underlying drug resistance mechanisms in gliomas.